Undertaking sensitive research in the health and social sciences managing boundaries, emotions and risks - Dickson-Swift, Virginia (Cambridge University Press, 2008)
Undertaking qualitative research on sensitive topics often raises a variety of ethical problems. Based on empirical research, this book documents experiences throughout the entire research process: from conceptualization, ethics approval, fieldwork, to analysis and publication. It presents readers with stories from the researcher's perspective and synthesizes these experiences into a conceptual framework that will assist researchers to undertake qualitative research. Each section discusses potential pitfalls, provides quotes and stories and reviews the relevant literature and theory, providing readers with a description of the process of conducting sensitive research from the perspective of those actually doing the research. This is not a methodology textbook, rather, it discusses the issues faced by researchers during the conduct of qualitative research on sensitive topics, such as death and dying, sexuality, homelessness, HIV/AIDS, cancer. It provides practical recommendations for researchers and Research Ethics Committees. It will also be a useful resource for anyone interested in undertaking a research project on sensitive topics and for those teaching qualitative methods across a broad range of disciplines.